EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DAN TWO STAY TWOSTRAY (TSTS) DENGAN PENDEKATAN SAINTIFIK DITINJAU DARI GAYA BELAJAR SISWA - Rahman, Arif; Budiyono, Budiyono; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract: The objective of this research was to investigate the effect of the learning models on learning achievement viewed from learning style types of the students. The learning models compared were NHT, TSTS, and classical with scientific approach model. The type of the research was quasi-experimental research with 3x3 factorial design. The population of this research was the students in grade X senior high school in Mataram City on academic year of 2014/2015. The size of the sample was 279 students, which was taken by using stratified cluster random sampling technique. The instruments used for data collection were learning style questionnaire and mathematics achievement test. The hypothesis test used unbalance two ways analysis of variance. The results of the research were as follows. (1) NHT and TSTS with scientific approach learning models gave better achievement than classical with scientific learning model. NHT and TSTS with scientific approach learning models gave the same achievement. (2) The students with visual and auditory learning style had better achievement than the students with kinesthetic learning style. The students with visual and auditory learning style had the same achievement. (3) In NHT with scientific approach learning model, the students with visual and auditory learning style the same achievement, the students with auditory and visual learning style had better achievement than the students with kinesthetic learning style. In TSTS and Classical with scientific approach learning models, the students with visual, auditory, and kinesthetic learning style the same achievement. (4) At the students with visual learning style, NHT and TSTS with scientific approach learning models gave the same achievement. NHT with scientific approach learning model gave better achievement than classical with scientific learning model. TSTS and classical with scientific approach learning models gave the same achievement. At the students with auditory and kinesthetic learning style, NHT, TSTS, and classical with scientific approach learning models gave the same achievement.Keywords: Numbered Heads Together, Two Stay Two Stray, Classical learning model, Scientific Approach, Learning Style, Achievement.